2011
DOI: 10.1111/j.1477-9552.2011.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Food Certification Costs Misestimated? Exporter-Perspective on the European Standard

Abstract: Food safety regulations aimed at controlling food contamination have sometimes been criticised as excessive burdens, disadvantaging smaller firms and exports from developing nations. Reported food safety expenditures appear relatively small (from <1 to 7% of the value of production) but can erode profit margins for many firms. This article responds to claims that reported firm‐level expenditures do not reflect true costs of compliance with food safety systems. We estimate incidental cost savings and uncounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Using a translog cost function, Maskus et al (2013) estimated that a 1 % increase in the direct cost of compliance results in a 0.06-0.13 % increase in firms' operational cost (net of the compliance cost) depending on the industry. This estimate seems much smaller than that of Ragasa et al (2011), possibly because the latter focused on the seafood sector whose assurance of food safety (under the requirement for the HACCP) would be by far more costly. Chen et al (2008b) estimated firm-level export functions of intensive and extensive margins.…”
Section: Firm-level Analysis Of the Impact Of Food Safety Standardsmentioning
confidence: 55%
See 1 more Smart Citation
“…Using a translog cost function, Maskus et al (2013) estimated that a 1 % increase in the direct cost of compliance results in a 0.06-0.13 % increase in firms' operational cost (net of the compliance cost) depending on the industry. This estimate seems much smaller than that of Ragasa et al (2011), possibly because the latter focused on the seafood sector whose assurance of food safety (under the requirement for the HACCP) would be by far more costly. Chen et al (2008b) estimated firm-level export functions of intensive and extensive margins.…”
Section: Firm-level Analysis Of the Impact Of Food Safety Standardsmentioning
confidence: 55%
“…The compliance cost seems to be not prohibitively high, but it still reduces the firm's ability to export, thereby constituting a barrier to trade. Ragasa et al (2011) assessed the magnitude and sign of the effect of firms' compliance to food safety regulations using survey data from seafood production firms in the Philippines. They calculated the expenditure to comply with the HACCP standards.…”
Section: Firm-level Analysis Of the Impact Of Food Safety Standardsmentioning
confidence: 99%
“…These bans resulted in substantial losses for the industries involved (Cato and Subasinge, 2003;Henson and Mitullah, 2004;Calvin et al, 2002). New U.S. seafood regulations in the 1990s imposed significant costs on exporting firms and limited market participation in two major exporting countries, the Philippines (Ragasa et al, 2011) and Brazil (Donovan et al, 2001).…”
Section: Food Safety Compliance For High Value Markets Provides Lessomentioning
confidence: 98%
“…Literature in strategic management identifies managerial hubris as a major cause of adverse firm performance, especially in explaining the failure of major strategic moves, such as mergers and acquisitions, or decreases in firm profitability (Roll 1986;Jiang et al 2011). Other studies suggest that firms often misestimate costs of regulations including those for food safety (Joshi et al 2001;Morgenstern et al 2001;Ragasa et al 2011b. Prior to certification, the actual costs and benefits to a firm are not known.…”
Section: Strategic Managementmentioning
confidence: 99%
“…Some studies have suggested that food producers and processors do not always embrace HACCP with the anticipated enthusiasm (Maldonado-Siman et al 2014;Taylor and Taylor 2004;Panisello and Quantick 2001). There is growing number of studies detailing the costs of HACCP compliance (Maldonado-Siman et al 2014;Handschuch et al 2013;Ragasa et al 2011b). Prior literature has identified a number of factors that affect initial adoption of HACCP, including length of time to develop and implement the program, technical expertise and support, availability of human resources, production technology and design, company size, and level of institutional support (Wallace et al 2014;Dzwolak 2014;Green and Kane 2014;Fotopoulos and Kafetzopoulos 2011).…”
mentioning
confidence: 99%